Deceleration of droplets that glide along the free surface of a bath. (19th August 2016) - Hale, Jacob; Akers, Caleb
Abstract : A droplet obliquely impacting a bath surface of the same fluid can traverse along the interface while slowing at an exponential rate. The droplet rests on a thin film of air, deforms the bath surface creating a dimple and travels along the surface similarly to a wave pulse. Viscous coupling of the droplet and bath surfaces through the air film leads to viscous drag on the bath and perturbs the wave motion of the otherwise free surface. Even though the Reynolds numbers are greater than unity ( $Re\, O(10{-}100)$ ), we show that the droplet's deceleration is only due to viscous coupling through the air gap. The rate of deceleration is found to increase linearly with droplet diameter.